MEMAHAMI ISLAM LOKAL MELALUI KITAB SERIBU MASA’IL: STUDI KOMPARASI TEKS ARAB-MELAYU - Alindah, Lutfiyah (Universitas Negeri Surabaya, 2015)
TheÂ spreadÂ andÂ developmentÂ ofÂ IslamÂ inÂ theÂ IndonesiaÂ notÂ onlyÂ brought Islam together, but also brought Islamic culture in the form of literature. The developmentÂ in teaching IslamicculturalÂ traditionÂ isÂ importantÂ inÂ the process of Islamization.Â ManyÂ booksÂ wereÂ translated,Â composedÂ orÂ adaptedÂ toÂ many languages in the archipelago. The books are compiled in what is known as sastra kitabÂ (literatureÂ ofÂ IslamicÂ theology).Â ItsÂ twoÂ versions,Â theÂ MasailÂ Sayyidi 'Abdullah bin SalamÂ lin NabiÂ inÂ the Arabic version orÂ Seribu Masaâ€™ilÂ in Malay version,Â areÂ stillÂ preserved.Â BothÂ ofÂ theseÂ textsÂ areÂ partÂ ofÂ theÂ processÂ of translationÂ fromÂ ArabicÂ textsÂ intoÂ MalayÂ textÂ whichÂ haveÂ variationsÂ eitherÂ in structureÂ linguisticÂ or meaning.ThisÂ paperÂ examinesÂ theÂ variationsÂ occurringÂ in process of translation between Arabic text and Malay text, and how the variations are manifestedÂ inÂ theseÂ twoÂ texts. ThisÂ researchÂ isÂ important becauseÂ itÂ looks at Sirah nabawiyah (history ofÂ the prophet)Â that documents both written and verbal teachingsÂ ofÂ Islam.Â InÂ addition,Â thisÂ studyÂ containsÂ theÂ theologicalÂ valuesÂ and dialogue between Muslims and non-Muslims. By using George Steinerâ€™sÂ theory, this study tries to examine the difficulties and the paradoxes created by translation fromÂ oneÂ languageÂ toÂ another.ThisÂ studyÂ demonstratesÂ thatÂ theÂ finalÂ translation between MasÄâ€™ilÂ SayyidiÂ â€˜AbdullÄhÂ BinÂ SalÄmÂ li-NabÄ«Â textÂ andÂ Seribu Masa'il have variations both in the structure of linguistics and meanings.Â